2008
DOI: 10.1016/j.ejcts.2008.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Residual apical space following surgery for pneumothorax increases the risk of recurrence

Abstract: The risk of recurrence after pneumothorax surgery is low. But the presence of a residual apical space on chest radiography after surgery increases it significantly. Recurrence may be due to the failure to achieve early pleural symphysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…Previous studies have reported that female sex, young age, smoking habit, presence of bilateral PSP, the area of RAS, the size and distribution of bullae, and incomplete bullectomy are risk factors for postoperative recurrence of PSP. 8,10,12,18,19) However, few previous studies have reported the impact of a change in the alveolar structure at the base of blebs and bullae on the recurrence of PSP after VATS bullectomy. Histological analysis of resected blebs and bullae is usually performed to identify unexpected lung diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that female sex, young age, smoking habit, presence of bilateral PSP, the area of RAS, the size and distribution of bullae, and incomplete bullectomy are risk factors for postoperative recurrence of PSP. 8,10,12,18,19) However, few previous studies have reported the impact of a change in the alveolar structure at the base of blebs and bullae on the recurrence of PSP after VATS bullectomy. Histological analysis of resected blebs and bullae is usually performed to identify unexpected lung diseases.…”
Section: Discussionmentioning
confidence: 99%
“…1a, 1d). The area of residual apical space (RAS) 10) on chest radiography at two weeks after VATS bullectomy was measured using Image J software (NIH Image J 1.48; National Institutes of Health, Bethesda, MD).…”
Section: Methodsmentioning
confidence: 99%
“…Regardless of stapling length, voluminous resection of the apical segment of the lung leaves a large residual apical space. Absence of pleural symphysis related to a residual apical space increases the risk of recurrence (8).…”
Section: Discussionmentioning
confidence: 99%
“…The goals of surgical treatment of pneumothorax are to identify and remove the source of air leakage and achieve pleural symphysis to minimize recurrence of the pneumothorax (8). Absence of pleural symphysis is associated with no formation of pleural adhesions and is related to early or late recurrent pneumothorax.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the presence of a residual pleural space after surgery may be one of the factors associated with increased risk of recurrence (14).…”
Section: B Regulated Suctionmentioning
confidence: 99%